2007
DOI: 10.2304/eerj.2007.6.4.364
|View full text |Cite
|
Sign up to set email alerts
|

The European eLearning Programme(s): Between rhetoric and reality

Abstract: This article presents the findings of a qualitative study conducted by the author on the implications of e-learning programmes for the higher education systems of the member states of the European Union. The study takes a look behind the scenes of the eLearning Programme and other elearning actions within other European programmes by tapping into the perceptions of academics at universities in the European Union (in three principal countries -Germany, Portugal and Swedenand six secondary countries -Belgium, Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…They are not doing a good job. So, if already there is little possibility and then we have underperforming projects, that is not a pity, but rather a waste As was the case with previous ICT initiatives, such as the eLearning Action Plan (Salajan, 2007(Salajan, , 2013, and with rhetorical discourse now familiar in policy narratives on the EU (Salajan, 2018), the DEAP uses the urgency of action to meet the challenges stemming from the rise of artificial intelligence and the prospect of big data, predictive analytics, the Internet of things, blockchain, etc., impacting human agency in socioeconomic and educational | 599 SALAJAN domains. Although the nature and sophistication of technologies have advanced, the challenges are similar to those addressed in the eLearning Action Plan or the eLearning Programme.…”
Section: The Third Wave: the Next Generation Of Ict Policy (2013 Onmentioning
confidence: 99%
“…They are not doing a good job. So, if already there is little possibility and then we have underperforming projects, that is not a pity, but rather a waste As was the case with previous ICT initiatives, such as the eLearning Action Plan (Salajan, 2007(Salajan, , 2013, and with rhetorical discourse now familiar in policy narratives on the EU (Salajan, 2018), the DEAP uses the urgency of action to meet the challenges stemming from the rise of artificial intelligence and the prospect of big data, predictive analytics, the Internet of things, blockchain, etc., impacting human agency in socioeconomic and educational | 599 SALAJAN domains. Although the nature and sophistication of technologies have advanced, the challenges are similar to those addressed in the eLearning Action Plan or the eLearning Programme.…”
Section: The Third Wave: the Next Generation Of Ict Policy (2013 Onmentioning
confidence: 99%
“…Current research on e‐learning policies in the EU consists of a combination of policy analysis and technical evaluation, exploring both supranational and national levels of policy influence. Thus, a number of studies suggested that the European Commission's policies stimulated collaboration in e‐learning approaches throughout the EU, but that their overall impact on the educational systems of the Member States was limited, largely because of the weak sustainability of projects designed via the e‐learning programmes operating under these policies (Dondi, Szücs & Wagner, ; Hodgson, ; Uzunboylu, ; Salajan, , ). Other studies have pointed to a need for closer alignment of national e‐learning policies with those formulated at EU level (Brown, Anderson & Murray, ; Goeman, ; Németh, ).…”
Section: E‐learning Policy Research Contextmentioning
confidence: 99%
“…As such, these policies strive to complement policies at Member State level, in accordance with the principle of subsidiarity enshrined in the Treaty on the European Union (TEU). E‐learning policy formulation has relatively recently become a domain of interest for the European Commission, mainly as a result of the initially disparate approaches to the integration of information and communication technology (ICT) in education at Member State level (Salajan, , ). In the last two decades, a greater involvement of the European Commission can be observed in initiating, drafting and proposing policies that include ideas for a more cohesive approach to ICT implementation in the educational systems of the Member States.…”
Section: Introductionmentioning
confidence: 99%
“…Proof that a process of accruing jurisdiction for e‐learning policy actions is taking place at Community level can be found in the e Learning Action Plan, which operationalised the terms of the Initiative between 2001 and 2003, and its successor, the e Learning Programme, which extended into further areas of concern for the educational use of ICTs between 2004 and 2006 (Salajan, 2007a; 2007b). Here, I only refer to the policy formulation for Community involvement in e‐learning mentioned in these documents to underline EELA's legal framework.…”
Section: Contours Of a European E‐learning Areamentioning
confidence: 99%
“…However, the boost in Community monitoring for e-learning is partly a process in its own right, since e-learning actions infiltrate other sectors in which ICTs support critical and routine tasks, whether they relate to office environments, social situations or industrial settings. Proof that a process of accruing jurisdiction for e-learning policy actions is taking place at Community level can be found in the eLearning Action Plan, which operationalised the terms of the Initiative between 2001 and 2003, and its successor, the eLearning Programme, which extended into further areas of concern for the educational use of ICTs between 2004 and 2006 (Salajan, 2007a;2007b). Here, I only refer to the policy formulation for Community involvement in e-learning mentioned in these documents to underline EELA's legal framework.…”
Section: Formal Legislationmentioning
confidence: 99%